Pengaruh peranan audit internal, sistem pengendalian internal, dan kompetensi staf akuntansi terhadap kualitas laporan keuangan - Budiantoro, Harry; Junika , Windy; Lapae, Kanaya; Ningsih , Hestin Agus Tantri; Primadini, Adinda (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The goal of this study was to look into the impact of internal audit, the role of the internal control system, and accounting staff competence on the quality of financial reports. The primary data in this study came in the form of a questionnaire. Respondents to this survey are internal auditors, accounting department personnel, and other personnel involved in knowing or compiling Bank Syariah Mandiri's financial statements. The number of respondents in this study was 70, based on the saturated sampling method. According to the findings of this study, the role of internal audit, internal control systems, and accounting staff competence all have a significant impact on the quality of financial reports.